The Relationship Between the Healthy Indonesia Program With a Family Approach and Infant Mortality Rate (IMR) in Karang Baru Subdistrict, Aceh Tamiang Regency - Zulfanda Manik; Muhammad Badiran; Anto J. Hadi (PT Yapindo Jaya Abadi, 2025)
The Healthy Indonesia Program is one program that aims to improve the quality of life of Indonesian people, improve the health status and nutritional status of the community through health efforts and community empowerment supported by financial protection and equitable distribution of health services. The general objective of this research is to analyze the policy relationship between the Healthy Indonesia Program and the Family Approach to Infant Mortality Rate (IMR) in Karang Baru Subdistrict, Aceh Tamiang Regency.This type of research is an analytic survey with a cross sectional study design. The study was conducted in Karang Baru Subdistrict, Aceh Tamiang Regency by using Simple Random Random Sampling technique, namely 66 mothers who had children under five. Chi Square test and logistic regression were used to analyze the data. Based on the results of the study note that the Infant Mortality Rate (IMR) is related to families participating in Family Planning (p = 0.020), mothers giving birth in health facilities (p = 0.024), infants receive complete basic immunizations (p = 0.006), utilization (breast milk) exclusive (p = 0.038), monitoring of toddler growth (p = 0,000). Based on the results of the study, it can be concluded that the factors related to Infant Mortality Rate (IMR) are families who participate in Family Planning, mothers deliver at health facilities, infants get complete basic immunizations, exclusive use (ASI), monitoring the growth of infants. So that the suggestions in this research are expected to be able to be material and input in the policy making of the Healthy Indonesia program with the Family Approach that health is a community right. Keywords: Healthy Indonesia Program Policies, IMR